Sentimen Analisis Masyarakat Indonesia di Twitter Terkait Metaverse dengan Algoritma Support Vector Machine - Ali Ahmad; Windu Gata (KITA Institute, 2022)
Metaverse is part of the increasingly rapid development of technology in the world, bringing the virtual world into the real world is very possible. Starting from a novel, metaverse has now begun the process of being implemented, especially with the COVID-19 pandemic being one of the strong foundations for speeding up the implementation of this technology. Since the emergence of the metaverse echoed by Facebook, which has changed its name to meta, has made the world's public attention increasingly highlight this technology, some have welcomed it and some have concerns about the development of this technology. Research to explore the sentiments of the Indonesian people towards metaverse technology uses the CRISP-DM method with the Support Vector Machine algorithm and the test is carried out by comparing it with another algorithm, namely the tree algorithm, the programming language used is the R language with the Rstudio application. This study obtained the results of Indonesian public opinion on metaverse technology which showed 66% to be neutral, 17% negative and 16% positive, while the results of testing with the SVM algorithm showed SVM performance results of 87% with the kernel used was Linear, and these results are far better than using the tree algorithm which only has a performance of 71%.